Statistical analysis of long term climatic data of Eastern Uttar Pradesh - Prince,; A. K. Singh,; S. R. Mishra,; A. N. Mishra,; Rajan Chaudhari, (The Bioscan, 2025)
The study analyzes long-term climatic variability in Eastern Uttar Pradesh, focusing on seasonal and annual variations in maximum and minimum temperatures and rainfall across three agroclimatic zones: Eastern Plain, North Eastern Plain, and Vindhyan Zone. Results indicate significant fluctuations, particularly in post-monsoon and winter seasons, where higher coefficients of variation were recorded for both temperatures and rainfall. Maximum temperature variability ranged from 0.3% to 6.3%, while minimum temperature variability reached up to 14.2%, especially in winter months. Annual rainfall also showed considerable variation, with coefficients ranging from 0.1% to 43.8% across zones and years. These climatic irregularities are likely to impact key crops like rice and wheat, increasing vulnerability during critical growth stages. The findings underline the urgency for adopting climate-resilient agricultural practices, improved irrigation management, and region-specific crop planning. Addressing this rising agroclimatic instability is essential to ensure sustainable agricultural productivity and food security in Eastern Uttar Pradesh.